Use of Cl/Br Ratio to Decipher the Origin of Dissolved Mineral Components in Deep Fluids from the Alps Range and Neighbouring Areas - Sonney, Romain; Vuataz, François; Cattin, Stéphane (My University, 2010)
Cl/Br ratios were studied in deep groundwaters to decipher the origin of dissolved mineral components from the Alps and neighbouring areas. Cl/Br molar ratio represents a good marker to define if the salinity comes from seawater or residual brines (655 and lower) or from dissolution of halite or halite-rich gypsum, often present in the Triassic formations (upper than the seawater ratio). It can be an interesting tool for projects dealing with exploration and production of geothermal fluids. Results of this study showed the presence of trapped seawater in formations of the large basins from the Quaternary to the basement, resulting from infiltration during different marine intrusion periods. This method also showed the presence of brines in crystalline aquifers. Some of these waters discharge along subvertical faults and are diluted to various degrees by different types of meteoric waters. In some cases, this method raises new questions about the true geological origin of deep circulations.
Keywords: Cl/Br ratio; hydrochemistry; hydrogeology; geothermal fluids; seawater brines; halite dissolution; Alps range